A Whole Blood Assay of Inhibition of Platelet Aggregation by Glycoprotein IIb/IIIa Antagonists: Comparison with other Aggregation Methodologies - Storey, Robert F.; May, Jane A.; Wilcox, Robert G.; Heptinstall, Stan (Thrombosis and Haemostasis, 1999)
We have used a whole blood single-platelet counting assay (WBSPC) that is sensitive to microaggregation for monitoring GPIIb/IIIa antagonists and have compared this with other methodologies. In vitro effects of the GPIIb/IIIa antagonist fradafiban on ADP-induced platelet aggregation were determined using WBSPC and PRP turbidimetry, comparing citrate and hirudin anticoagulation. Fradafiban was a more potent inhibitor of aggregation assessed by PRP turbidimetry compared to WBSPC. Citrate showed only a trend towards enhancing fradafiban potency (p = 0.087). Citrated blood from 8 patients with unstable angina, randomised to receive oral lefradafiban (the oral prodrug of fradafiban) or placebo, was studied before and during treatment using WBSPC, PRP turbidimetry, impedance aggregometry and Rapid Platelet Function Assay (RPFA, Accumetrics). RPFA, PRP turbidimetry and WBSPC measurements correlated well. Impedance aggregometry responses were oversensitive to GPIIb/IIIa blockade. WBSPC was most discriminating at high levels of inhibition and offered a rapid means of monitoring GPIIb/IIIa antagonist effect within the therapeutic range of inhibition.
Keywords: Platelet aggregation; platelet aggregation inhibitors; unstable angina